2017
DOI: 10.1038/jp.2017.80
|View full text |Cite
|
Sign up to set email alerts
|

Risk of nonsteroidal anti-inflammatory drug-associated renal dysfunction among neonates diagnosed with patent ductus arteriosus and treated with gentamicin

Abstract: Among neonates with PDA and receiving gentamicin, NSAID therapy increases the risk of AKI by about 6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 62 publications
0
11
1
Order By: Relevance
“…PDA may impair the kidney perfusion and thus lead to a decreased clearance of aminoglycosides 24,25 ; aminoglycosides themselves are supposed to be nephrotoxic, 26 and nonsteroidal anti-inflammatory drugs may further increase the nephrotoxic risk by decreasing renal perfusion. 16,27 In our cohort, we did not find a higher mortality in infants treated with ampicillin and cefotaxime, which Clark et al 10 found in a cohort of 128 914 neonates admitted to a NICU. On the contrary, we found a lower mortality in those NICUs, which used other than aminoglycosides as first-line antibiotics.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…PDA may impair the kidney perfusion and thus lead to a decreased clearance of aminoglycosides 24,25 ; aminoglycosides themselves are supposed to be nephrotoxic, 26 and nonsteroidal anti-inflammatory drugs may further increase the nephrotoxic risk by decreasing renal perfusion. 16,27 In our cohort, we did not find a higher mortality in infants treated with ampicillin and cefotaxime, which Clark et al 10 found in a cohort of 128 914 neonates admitted to a NICU. On the contrary, we found a lower mortality in those NICUs, which used other than aminoglycosides as first-line antibiotics.…”
Section: Discussioncontrasting
confidence: 45%
“…Acute kidney injury was associated with gentamicin use and birthweight. PDA may impair the kidney perfusion and thus lead to a decreased clearance of aminoglycosides 24,25 ; aminoglycosides themselves are supposed to be nephrotoxic, 26 and nonsteroidal anti‐inflammatory drugs may further increase the nephrotoxic risk by decreasing renal perfusion 16,27 …”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Hence these eight studies were excluded from this meta-analysis as well. The remaining seven studies (four case-control studies and three retrospective cohort studies) [27][28][29][30][31][32][33] examining NSAID-associated AKI risk in 54 852 hospitalized pediatric patients met our inclusion criteria (Figure 1). The detailed characteristics and Newcastle-Ottawa quality assessment scale of all included studies were described in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies 30,33 reported integrated NSAIDs use OR while the other five studies [27][28][29]31,32 only reported individual NSAID-related risks (three studies reported two individual medications and two studies focused on ibuprofen singly). We analyzed the ORs of these five studies with the same method: We considered the OR of each individual medication as the OR of an independent separate study.…”
Section: Resultsmentioning
confidence: 99%
“…The newborn kidney is particularly vulnerable to maldevelopment and dysfunction in an ex utero environment due to various stresses, mostly caused by decreased renal perfusion [23]. In a few studies, nephrotoxic injury is usually associated with the use of NSAID to close a PDA, especially with concomitant use of aminoglycosides [8,34,35]. However, the attributable risk of AKI associated with these 2 nephrotoxic agents is not clear.…”
Section: Discussionmentioning
confidence: 99%